Utility of CD4 Cell Count and Viral Load Assay in Hospitalized Patients with Known HIV Infection: High Value Care Exercise - Lal, Amos; Abraham, George M. (Infectious Disorders - Drug Targets, 2020)
Purpose: Healthcare spending as a percentage of Gross domestic product (GDP) is at all-time high and continues to rise in the United States. The Centers for Medicare and Medicaid Services estimate that 33% of resources spent on healthcare goes to waste. As part of a ‘high value care’ exercise, we studied if estimating CD4 cell counts and HIV viral load in hospitalized patients with a known diagnosis of HIV led to any meaningful change in HAART regimen and discharge diagnosis. Methods: Retrospective chart review for all patients admitted with a known diagnosis of HIV from January 1, through December 31, 2017. Results: A total of 83 patient encounters were reviewed during the period. The mean age was 54.1 ± 16.4 years, 64.1 % of patients were males. 75 patients (90.3%) were already on highly active antiretroviral therapy (HAART). The median hospital length of stay (LOS) was 3 days (IQR 2.0 - 5.0). The mean turnaround time for CD4 counts and HIV viral load assay was 2.9 days (95% CI 2.1 – 3.7) and 3.9 days (95% CI, 3.2 – 4.6), respectively. A CD4 count estimation led to no change in HAART regimen. HIV viral load assay testing had no impact on a change in treatment or a change in diagnosis. Conclusions: In our study, testing CD4 counts and HIV viral load for inpatients did not confer any benefit in altering the diagnosis or HAART regimen. We believe that our study identifies a systems level opportunity to add to the concept of ‘Choosing Wisely.’
Keywords: antibiotics